The relationship of treatment type and epithelial / subepithelial changes in healed dudenal ulcers - Melih ÖZEL; Levent DEMİRTÜRK and Ahmet Kemal GÜRBÜZ and Ergun UÇMAKLI and Yusuf YAZGAN and Mehmet DANACI (Turkish Journal of Gastroenterology, 2019)
-